Pinch, cinch or step: Evaluating the effectiveness and acceptability of mid upper arm circumference measurements in adolescents with eating disorders. (August 2016) - Lam, Pei-Yoong; Marshall, Sheila K.; Devi Harjit, Geetha; Coelho, Jennifer S.; Cairns, Jadine
Abstract: Purpose: Mid Upper Arm Circumference (MUAC) measurement is proposed as an adjunctive measure of re-nutrition progress in youth with eating disorders. We propose that MUAC is a clinically-useful measurement that can be used to inform clinicians about treatment progress. The aims of this study were twofold: 1) to test whether assessments of MUAC can track weight restoration in a similar pattern to direct measures of weight and 2) to examine adolescents' self-reported feelings in response to assessments of MUAC, weighing, and skinfolds (SF). Methods: The study involved two phases of data collection. Participants in both phases of the study were female patients who fulfilled DSM IV-TR diagnostic criteria for an eating disorder. In Phase 1, MUAC measurements and weight assessments were collected weekly to examine changes in these values during the first 8 weeks of treatment. In Phase 2, participants reported their feelings towards three different anthropometric measures — weight, SF and MUAC. Results: Simple contrasts between the weekly weight and MUAC assessments prospectively collected in Phase 1 (N = 40) reveal that MUAC and weight follow similar patterns over time. Phase 2 (N = 30) data indicate that participants felt more relaxed, and less angry, scared or embarrassed during MUAC measurements than weighing and SF. MUAC also emerged as the measurement that was most preferred by participants. Conclusions: MUAC measurements are a useful adjunct to measurements of weight, and are perceived to be less distressing than routinely used measurement techniques of weight and SF. Highlights: Mid-upper Arm Circumference (MUAC) tracks change in a similar pattern as weight in female adolescents treated for eating disorders. Discrepancies between changes in weight and MUAC can highlight possible weight falsification. MUAC measurements were better tolerated emotionally than weight and skinfold measurements. MUAC appears to be a useful adjunct to weight for tracking physical recovery.